High-Sensitivity Wearable and Flexible Humidity Sensor Based on Graphene Oxide/Non-Woven Fabric for Respiration Monitoring - Wang, Yamei (Langmuir : the ACS journal of surfaces and colloids, 2020)
The popularity of humidity sensing for respiratory analysis of patients is gradually increasing because of its portability and cost-effectiveness. However, current flexible humidity sensors are mainly made of polymer films, whose poor hygroscopicity and breathability reduce their sensitivity and comfort. In this study, a highly sensitive humidity sensor was developed using non-woven fabric (NWF) coated with graphene oxide (GO). Bovine serum albumin was used to improve the adsorption of GO onto the NWF, and its effect on sensitivity was investigated by adjusting its concentration. High-humidity sensitivity was experimentally validated by testing different relative humidity levels, and its fast response and excellent feasibility under diverse breathing conditions were verified by successful monitoring of fast and deep breathing, differentiating nose and mouth breathing, and even identifying simple spoken words. This study developed a breathable and skin-friendly humidity sensor based on GO/NWF, which is a promising device for human healthcare